2018
DOI: 10.1002/art.40672
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor Regulates U1 Small Nuclear RNP Immune Complex–Mediated Activation of the NLRP3 Inflammasome

Abstract: The U1 snRNP immune complex is a specific stimulus of MIF production in human monocytes, with MIF having an upstream role in defining the inflammatory characteristics of activated monocytes by regulating NLRP3 inflammasome activation and downstream IL-1β production. These findings provide mechanistic insight and a therapeutic rationale for targeting MIF in subgroups of lupus patients, such as those classified as high genotypic MIF expressers or those with anti-snRNP antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 56 publications
(94 reference statements)
2
58
0
1
Order By: Relevance
“…Similar to our observations, exogenous MIF did not activate NLRP3 in murine BMDM; however, endogenous MIF regulated NLRP3 in the assembly of inflammasomes [17]. Furthermore, a study using a murine systemic lupus erythematosus model confirmed that addition of exogenous rMIF alone did not induce NLRP3 in human monocytes [37]. Although exogenously added rMIF had no impact on monocyte IL-1b production in our model, MIF may act on other inflammatory pathways which were not investigated in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to our observations, exogenous MIF did not activate NLRP3 in murine BMDM; however, endogenous MIF regulated NLRP3 in the assembly of inflammasomes [17]. Furthermore, a study using a murine systemic lupus erythematosus model confirmed that addition of exogenous rMIF alone did not induce NLRP3 in human monocytes [37]. Although exogenously added rMIF had no impact on monocyte IL-1b production in our model, MIF may act on other inflammatory pathways which were not investigated in this study.…”
Section: Discussionsupporting
confidence: 86%
“…In turn, a variety of signaling cascades, including the MAPK, PI3K/AKT, and NF-kB pathways are activated. By doing so, MIF activates pro-inflammatory events including the secretion of IL-6 and TNF-α and the activation of the inflammasome [29][30][31].…”
Section: Biology Physiology and Physiopathology Of Mifmentioning
confidence: 99%
“…Recently, the role of macrophage migration inhibitory factor (MIF) in up‐regulating NLRP3 expression was demonstrated in human monocytes stimulated with the U1 snRNP lupus immune complex . Upon exposure to the latter, human monocytes produced MIF, and blocking MIF binding to its receptor CD74 suppressed NLRP3 expression and subsequent caspase 1 activation . The expression levels of MIF and CD74 correlated at the single cell level, supporting the autocrine and paracrine effects of MIF in regulating NLRP3.…”
Section: Introductionmentioning
confidence: 94%
“…Also, ATP‐induced IL‐1β production has been shown to be increased in the macrophages of patients with SLE . Recently, the role of macrophage migration inhibitory factor (MIF) in up‐regulating NLRP3 expression was demonstrated in human monocytes stimulated with the U1 snRNP lupus immune complex . Upon exposure to the latter, human monocytes produced MIF, and blocking MIF binding to its receptor CD74 suppressed NLRP3 expression and subsequent caspase 1 activation .…”
Section: Introductionmentioning
confidence: 99%